SSCANL decoder based joint iterative detection and decoding algorithm - Chongyang LIU; Rui GUO (Dianxin kexue)
In order to improve the receiver performance of the sparse code multiple access (SCMA) system based on polar codes, the cyclic redundancy check (CRC) aided joint iterative detection and decoding receiver scheme based on simplify soft cancellation list (SSCANL) decoder (C-JIDD-SSCANL) was proposed.A polar code decoder in the C-JIDD-SSCANL receiver used the SSCANL algorithm.In this algorithm, decoding node deletion technology was used to simplify L times of soft cancellation (SCAN) decoding required by soft cancellation list (SCANL) algorithm by deleting frozen bit nodes, then the computational process of soft information update between nodes was simplified, and the computational complexity of decoding algorithm was reduced.The simulation results show that the SSCANL algorithm can obtain the same performance as the SCANL algorithm, and its computational complexity is reduced compared with the SCANL algorithm.Compared with the joint iterative detection and decoding scheme based on SCAN decoder (JIDD-SCAN) and the CRC aided joint iterative detection and decoding scheme based on SCAN decoder (C-JIDD-SCAN), the performance of C-JIDD-SSCANL receiver scheme based on SSCANL decoder is improved by about 0.65 dB and 0.59 dB respectively when the bit error rate is 10-4.